Zirconium‐Catalyzed Atom‐Economical Synthesis of 1, 1‐Diborylalkanes from Terminal and Internal Alkenes. Issue 32 (27th May 2020) - Wang, Xianjin; Cui, Xin; Li, Sida; Wang, Yue; Xia, Chungu; Jiao, Haijun; Wu, Lipeng
Abstract: A general and atom‐economical synthesis of 1, 1‐diborylalkanes from alkenes and a borane without the need for an additional H2 acceptor is reported for the first time. The key to our success is the use of an earth‐abundant zirconium‐based catalyst, which allows a balance of self‐contradictory reactivities (dehydrogenative boration and hydroboration) to be achieved. Our method avoids using an excess amount of another alkene as an H2 acceptor, which was required in other reported systems. Furthermore, substrates such as simple long‐chain aliphatic alkenes that did not react before also underwent 1, 1‐diboration in our system. Significantly, the unprecedented 1, 1‐diboration of internal alkenes enabled the preparation of 1, 1‐diborylalkanes. Abstract : An earth‐abundant zirconium‐based catalyst has been developed for the selective 1, 1‐diboration of bulk and inexpensive alkenes with a borane without the need for an additional H2 acceptor. Many aryl alkenes as well as long‐chain aliphatic alkenes convert smoothly into their corresponding 1, 1‐diborylalkanes and the method also allows the unprecedented remote 1, 1‐diboration of internal alkenes.